2011
DOI: 10.1111/j.1523-5378.2011.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer: Clinical Aspects, Epidemiology and Molecular Background

Abstract: In 2010, the WHO introduced the seventh edition of the tumor node metastasis (TNM) classification that provides a more detailed classification for both local tumor invasion (T) and lymph node involvement (N) compared with the previous version. The T and N categories of tumors located in the stomach have been further modified with the intention to ensure a better correlation to the prognostic outcome. For the classification of a pN0, the number of lymph nodes has been adjusted to 16.The description of tumors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 64 publications
2
43
0
1
Order By: Relevance
“…Although distal gastric cancer incidence is decreasing in rich countries, it remains as a priority health problem in many countries all over the world [7,9,10]. Figure 2: A parametric T test for paired samples showed that no statistically significant difference was observed among nitrites levels before and after the washing procedures (p=0·807).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although distal gastric cancer incidence is decreasing in rich countries, it remains as a priority health problem in many countries all over the world [7,9,10]. Figure 2: A parametric T test for paired samples showed that no statistically significant difference was observed among nitrites levels before and after the washing procedures (p=0·807).…”
Section: Discussionmentioning
confidence: 98%
“…Salted foods and exposure to H. pylori infection during the infancy have been considered the most important environment risk factors for gastric cancer, and several new meta-analyses support the carcinogenic effect of high salt intake in the context of Helicobacter pylori infection [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal type develops through progressive changes in the gastric mucosa from non-atrophic gastritis (NAG), atrophic gastritis, intestinal metaplasia, dysplasia, and gastric cancer (11). It has been shown that eradication of the infection at an early stage can reverse gastric lesions and, more importantly, prevent the development of preneoplasia (7,12,13). A clinical study conducted in Japan demonstrated the efficacy of H. pylori eradication to reduce the incidence of gastric cancer (14) and confirmed that it was not enough to prevent all gastric cancer cases.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, after a complete resection, the 5-year survival rate remains low [3]. Several studies have shown that various genetic and epigenetic alterations are involved in the course of carcinogenesis and progression of gastric cancer [4][5][6]. However, the molecular mechanism involved in the development of gastric cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%